The Absent Father across Three Normative Orders: Legal Pluralism, Maqasid al-Shari'ah, and Meaning-Making in an Indonesian Pesantren - Muhammad Fauzan Aziman; Abdulnasir Dhaw Alsayd (PFL: Plural Family Law Review, 2026)
This article reports a single-site qualitative case study of fatherlessness, the absence of the father's role in physical or psychological terms, among the santri of one Islamic boarding school, Pondok Pesantren Darunnajah 1 in South Jakarta. Its scope is deliberately bounded: the findings describe this institution and are not advanced as conclusions about father absence in Indonesia generally, whose national scale remains contested. The study uses maqasid al-shari'ah deductively, as an a priori coding framework that organizes both the interview instrument and the analysis. It pursues three aims: to describe the role of the father as idealized in Islamic and Indonesian positive law; to analyze the positive and negative effects of father absence in a balanced rather than uniformly pathological way; and to map those effects across the five objectives of the shari'ah. Drawing on observation, semi-structured interviews with six santri who had experienced father absence, and documentation analyzed through the framework of Miles, Huberman, and Saldaña, the study finds that the father's role extends well beyond provision to leadership, motivation, spiritual guidance, and modeling; that the effects of father absence are not inherently negative but appear to be shaped by the individual's capacity for meaning-making and by the socio-spiritual environment of the pesantren; and that father absence touches all five objectives to varying degrees and directions. In this bounded setting, perspective and meaning-making emerge as decisive.